Characterization of the bacterial biofilm communities present in reverse-osmosis water systems for haemodialysis - Cuevas, Juan Pablo; Moraga, Rubén; Valenzuela, Cristian; Aguayo Venegas, Paulina Andrea.; Smith, Carlos T.; García, Apolinaria; Fernández, Ítalo; Campos, Víctor L.; Sánchez Alonzo, Kimberly. (MDPI, 2020)
"Abstract: Biofilm in reverse osmosis (RO) membranes is a common problem in water treatment at haemodialysis facilities. Bacteria adhere and proliferate on RO membranes, forming biofilms, obstructing and damaging the membranes and allowing the transfer of bacteria and/or cellular components potentially harmful to the health of haemodialysis patients. Our aim was to characterize the bacterial community associated to biofilm of RO membranes and to identify potentially pathogenic bacteria present in the haemodialysis systems of two dialysis centres in Chile. The diversity of the bacterial communities present on RO membranes and potable and osmosed water samples was evaluated using Illumina sequencing. Additionally, bacteria from potable water, osmosed water and RO membrane samples were isolated, characterized and identified by Sanger’s sequencing. The molecular analyses of metagenomics showed that the phyla having a greater relative abundance in both dialysis centres were Proteobacteria and Planctomycetes. Pseudomonas, Stenotrophomonas, Agrobacterium, Pigmentiphaga, Ralstonia, Arthrobacter, Bacteroides and Staphylococcus were bacterial genera isolated from the different samples obtained at both haemodialysis centres. Pseudomonas spp. was a bacterial genus with greater frequency in all samples. Pseudomonas and Staphylococcus showed higher levels of resistance to the antibiotics tested. Results demonstrated the presence of potentially pathogenic bacteria, showing resistance to antimicrobials on RO membranes and in osmosed water in both dialysis centres studied."
Keywords: Biofilm.; Biofouling.; Reverse osmosis membranes.; Haemodialysis.; Metagenomics.